GAMBARAN KARAKTERISTIK IBU HAMIL YANG BERPOTENSI MENGALAMI HIPEREMESIS GRAVIDARUM PASCA PANDEMI COVID 19 DI PUSKESMAS TAMALANREA JAYA - Munawwarah. M, St.; Susanto, Yoan Putri Praditia; Salim, Agus (JURNAL KESEHATAN DELIMA PELAMONIA, 2025)
Background The characteristics of pregnant women who are at risk of experiencing hyperemesis gravidarum after the COVID-19 pandemic are influenced by several factors such as age, parity, pregnancy interval, and education level. These factors can contribute to a decrease in maternal body weight, potentially leading to dehydration and hemoconcentration, which in turn can slow down blood circulation. The exact cause of hyperemesis gravidarum remains unknown, but it is believed to be associated with first-time pregnancies; hormonal surges during pregnancy—especially in cases of multiple pregnancies or molar pregnancies; maternal age under 24 years; metabolic changes during pregnancy; allergies; and psychosocial factors. Women with a history of nausea during previous pregnancies and those who are obese also show an increased risk of experiencing hyperemesis gravidarum. Research Objective This study utilized a cross-sectional research design. A cross-sectional study is an observational (non-experimental) method that is primarily descriptive but can also be analytic in nature. In this design, all variables are measured at a single point in time, making it a type of prevalence study. The sample was selected based on specific characteristics within the population that have dominant relationships, which helped in achieving the research objectives and determining predefined criteria based on the variables studied. The data collected were analyzed using the Chi-Square test, and the results were processed to determine the relationship between the independent variables and the dependent variable. The findings showed a significant association between age and hyperemesis gravidarum (p=0.001); parity and hyperemesis gravidarum (p=0.004); pregnancy interval and hyperemesis gravidarum (p=0.004); and education level and hyperemesis gravidarum (p=0.006). In conclusion, there are multiple factors that influence the likelihood of pregnant women developing hyperemesis gravidarum.